(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
The use of Bacillus thuringiensis as biological control has been poor in Venezuela and even has a bank of native strains with toxic potential on various insect pests but its evaluation has been partial. The objective of this work was to characterize morphologically and molecularly natives strains of Venezuela toxic of B. thuringiensis against P.operculella from the potato crop. The strains UCLABt- 01, UCLABt- 44, UCLABt- 64, UCLABt- 67, UCLABt- 202, UCLABt- 204. As control strain was used B. thuringiensis var. kurstaki (HD-1) were analyzed by studies of transmission for morphological characterization of the crystals were performed. For identification of genes cry1Ac did use the PCR technique using the primers CJ-1 y CJ-2,19. Identify the gene encoding the toxin against the insect. All strains showed parasporal inclusion of bipyramidal form, typical of patotipo I, a Lepidopteran toxic. The gene content analysis by PCR showed that all amplification profiles were obtained with specific primers for the gene cry Ac including positive control except UCLABt-64 strain. Gene content is not definitive by itself, the track recommends standardizing and others how to use initiators cry9A, cry 9B y cry 9C, cry 9A, cry 9B y cry9C, could indicate the presence of additional genes to those found cry.